Statistical models for risk management - Knight, John (Henry Stewart Talks, 2007)
Definition of returns: simple returns and log returns, Distribution of returns, univariate: normal and log-normal distribution, Stylized facts of historical returns, Skewness, kurtosis, autocorrelation and stationarity, ARCH, GARCH and stochastic volatility (SV) models, Distribution of returns, multivariate: multivariate normal distribution, Multivariate GARCH and SV models, Copulas and non-linear dependence
Archived at 2022/04/04